Ceratonia siliqua L. hydroethanolic extract obtained by ultrasonication: antioxidant activity, phenolic compounds profile and effects in yogurts functionalized with their free and microencapsulated forms. Issue 3 (18th February 2016) - Rached, Irada; Barros, Lillian; Fernandes, Isabel P.; Santos-Buelga, Celestino; Rodrigues, Alírio E.; Ferchichi, Ali; Barreiro, Maria Filomena; Ferreira, Isabel C. F. R.
Abstract : Microencapsulated polyphenols extracted from carob pulp are a viable functional ingredient for the food industry. Abstract : Bioactive extracts were obtained from powdered carob pulp through an ultrasound extraction process and then evaluated in terms of antioxidant activity. Ten minutes of ultrasonication at 375 Hz were the optimal conditions leading to an extract with the highest antioxidant effects. After its chemical characterization, which revealed the preponderance of gallotannins, the extract (free and microencapsulated) was incorporated in yogurts. The microspheres were prepared using an extract/sodium alginate ratio of 100/400 (mg mg −1 ) selected after testing different ratios. The yogurts with the free extract exhibited higher antioxidant activity than the samples added with the encapsulated extracts, showing the preserving role of alginate as a coating material. None of the forms significantly altered the yogurt's nutritional value. This study confirmed the efficiency of microencapsulation to stabilize functional ingredients in food matrices maintaining almost the structural integrity of polyphenols extracted from carob pulp and furthermore improving the antioxidant potency of the final product.